Philosophical Values for Children's Legal Rules in the Positive Law of Islam Indonesia - Nurhadi Nurhadi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Abstract The obligation to provide for a child is prioritized by a father, but if it is not capable, then the mother will take it. Ages earn a living from 0 to 21 years or get married. If a civil servant then the child salary is 1/3. The philosophy of child care obligations in Islamic UUP, if viewed from the axiological aspect of the benefit of the law, then the livelihood of children is a medium to achieve people's welfare, with the fulfillment of children's livelihood means that they have prepared quality human resources in the future, because in their livelihood three children aspects of fulfilling basic needs of children, namely primary needs, children's spiritual (psychological) needs and children's intellectual needs. From the axiological aspect of legal justice, the fulfillment of children's livelihood is full of the values of theological justice, social justice and gender justice. Whereas from the axiological aspect of legal certainty, the existence of legal sanctions on family law legislation serves as social control as a preventive measure to prevent acts of neglect of the child and repressive (forcing) parents to provide for the child by paying them later, as guarantee of child rights (child rights).